(untitled) (International Journal of Innovative Research in Engineering & Management, 2024)
In this paper the authors present the outcome of an experimental maintenance and reliability investigation conducted to prevent operation failure of pinion bearings caused by excessive temperature with a case study of a 1360kW ball mill driveline system in mineral processing application. Aiming to improve the overall plant performance, the lubrication regime of pinion bearings as key component within the ball mill driveline system was studied to determine possible causes of temperature increase at 80 to over 100C with a 25 - 30C gap over the maximum operating temperature. An analytical review of maintenance data is conducted to mitigate future operational risks by implementing a new lubrication regime and shutdown frequency for overall statutory inspection. Accelerated life test based inverse power law has been applied to identify the root causes of excessive bearings temperature to establish immediate short-term solution paths towards a guaranteed less required maintenance asset improvement practice, less operational cost, and plant availability enhancement. Furthermore, long-term solutions have been proposed based on modelling by thermal network approach of pinion bearings for thermomechanical stress prevention. A single parameter based accelerated test on pinion bearings was applied to establish operational fault tolerant factors to be considered for asset capability improvement, which remains an open question for future studies. These actions have shown significant improvement with temperature decrease between 15 and 25C below the maximum required temperature.